Catching up with the Past: A Small Contribution to a Long History of Interactive Environments - Michael Fox (Footprint)
This paper documents the evolution of my thinking in the area of interactive architecture over the past 15 years with students and my office. The work is framed within an overview of a long history of work in the area by others. My personal development has taken a number of clear steps in a relatively logical progression.